ANALISIS EFEKTIVITAS PENGELOLAAN DANA DESA UNTUK PEMBANGUNAN DAN PEMBERDAYAAN MASYARAKAT DESA DI KABUPATEN MINAHASA TENGGARA - Adi Yusmana Rogahang; Anderson G. Kumenaung; Ita P. Fasnie Rorong (Universitas Sam Ratulangi, 2022)
This study aims to determine (1) The Effect of Demographic and Geographical Factors on the Effectiveness of Village Fund Management during The pandemic in Southeast Minahasa Regency. (2) To determine the effectiveness of The Village Fund, it can be seen from the allocation of Village Funds and Village Performance in improving the village economy.This research uses Multiple Linear Regression analysis method. Data collection techniques are interviews, observation guides and documentation. Data used: working paper for calculating village funds and APBDes posture in the form of income, expenditure and financing. Data analysis uses Multiple Linear Regression analysis.The results of this study are: (1) Partially there is a significant and positive relationship between the ratio of population, poor population and the ratio of area to Village Fund management in Southeast Minahasa Regency; On the other hand, the Geographical Difficulty Index partially has no significant effect on the management of the Village Fund; (2) Together, the population ratio, poor population ratio, area ratio and Geographical Difficulty Index (IKG) have a significant effect on the management of Village Funds with the largest influence being the ratio of population to village fund management in the field of development and empowerment of rural communities; (3) Variations in changes in the effectiveness of Village Fund management 97.17% are caused by variations in changes in the four independent variables selected in this study; (4) The quality of Village Fund management in Southeast Minahasa Regency is at the VeryÂ Effective level. (5) There are 47 villages with developed status as seen from the independent village index, but the level of effectiveness of village fund management in Southeast Minahasa Regency still needs to be improved.Recommendations from this research for the village government in the future can provide policies on the management and distribution of Village Funds and the recording of Village Assets while still paying attention to strengthening the role of government institutions in the village. Transparency of village budget management to government institutions in the village in various fields so that the Village Funds are distributed according to what has been planned.